PENGARUH DEMOGRAFI, PENGALAMAN BEKERJA, DAN PENDIDIKAN PENGELOLAAN KEUANGAN ORANG TUA TERHADAP LITERASI KEUANGAN MAHASISWA DI PERGURUAN TINGGI SURABAYA - HAMZAH RIZALDI, MUHAMMAD; ASANDIMITRA HARYONO, NADIA (Jurnal Ilmu Manajemen (JIM), 2018)
Financial literacy is a very influential thing in economic development in Indonesia. This study aims to analyze the influence between gender, age, income, GPA, work experience, and education on parents financial management of student financial literacy in universities in Surabaya. This type of research is qualitative research with a total sample of 250 respondents. The object of this research is college students in Surabaya. The data analysis technique used is multiple linear regression analysis and uses IBM SPSS version 24. The results of the study are that there is no effect between the gender on financial literacy on students in Surabaya, this is because both women and men have an average education graduated from high school because the research respondents were students so their thinking was not much different. There is no effect between age on financial literacy on students in Surabaya, this is because the age of new or senior students can also understand financial literacy. There is a positive influence between income on financial literacy in students at universities in Surabaya. The higher the income earned by the individual, the easier it is for individuals to fulfill their needs. There is a positive influence between GPA on financial literacy on students in Surabaya universities, because the greater the GPA, the greater the understanding of financial literacy. There is no influence between the experience of working on financial literacy at students in Surabaya, because incidental or part time working time makes students not interact maximally in the environment.